Building Filipino Hawaiʻi - Labrador, Roderick N. (Urbana, Illinois : University of Illinois Press, 2015)
"Drawing on ten years of interviews and ethnographic and archival research, Building Filipino Hawai'i delves into the ways Filipinos in Hawai'i have balanced their pursuit of upward mobility and mainstream acceptance with a desire to keep their Filipino identity."--
Introduction: "Why do you want to go to Hawai'i?" -- Overlapping architectures -- "What's so p/funny?" -- "Anything but ..." -- "The center is not just for Filipinos, but for all of Hawai'i nei" -- Conclusion: Unsettling Hawai'i.
Includes bibliographical references (pages 149-161) and index.
Print version record.
JSTOR
Keywords: Filipinos -- Hawaii -- Social conditions; Asian Americans -- Hawaii -- Ethnic relations; Filipinos -- Hawaii -- History; Filipinos -- Hawaii -- Ethnic relations; Philippins -- Hawaii -- Conditions sociales; Américains d'origine asiatique -- Hawaii -- Relations interethniques; Philippins -- Hawaii -- Histoire; Philippins -- Hawaii -- Relations interethniques; SOCIAL SCIENCE -- Anthropology -- Cultural; Filipinos; Filipinos -- Social conditions; Hawaii; History